2022
DOI: 10.1111/1471-0528.17061
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic artery peak systolic velocity ratio distinguishes pre‐eclampsia from chronic and gestational hypertension: A prospective cohort study

Abstract: Objective: To examine whether the ophthalmic artery peak systolic velocity ratio (OA PSV-ratio) is higher in women with pre-eclampsia compared with gestational hypertension (GH) and chronic hypertension (CH), after controlling for confounding variables. Design: Prospective cohort.Setting: Specialist hypertension clinic in a tertiary referral centre.Population: Singleton pregnancies presenting between 32 +0 and 36 +6 weeks of gestation with pre-eclampsia (n = 50), GH (n = 54) and CH (n = 56).Methods: Paired mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…In this context, our team analysed OAD waveforms in 70 pregnant smokers and found an important modulation caused by cigarette use: a biphasic pattern of perfusion correlated with the time since the consumption of the last cigarette. This study is in agreement with that of Lau et al, 1 which also demonstrates that it is possible to perform non-invasive assessment of central nervous system arteries in pregnant women and test the action of vasoactive drugs. 4 We have also reported the accuracy and best cutoff value for OAD indices to diagnose pre-eclampsia.…”
Section: E T T E R T O T H E E D I T O Rsupporting
confidence: 93%
See 1 more Smart Citation
“…In this context, our team analysed OAD waveforms in 70 pregnant smokers and found an important modulation caused by cigarette use: a biphasic pattern of perfusion correlated with the time since the consumption of the last cigarette. This study is in agreement with that of Lau et al, 1 which also demonstrates that it is possible to perform non-invasive assessment of central nervous system arteries in pregnant women and test the action of vasoactive drugs. 4 We have also reported the accuracy and best cutoff value for OAD indices to diagnose pre-eclampsia.…”
Section: E T T E R T O T H E E D I T O Rsupporting
confidence: 93%
“…Ophthalmic artery Doppler in hypertensive pregnancies: Small vessel, many possibilities Dear Dr. Papageorghiou, We read with great interest the study by Lau et al, 1 and the excellent mini-commentary published by Gonser et al, 2 where we had the honour to be cited in the Acknowledgments. This motivated us to write a brief comment on the use of ophthalmic artery Doppler (OAD).…”
Section: E T T E R T O T H E E D I T O Rmentioning
confidence: 98%
“…
We thank Diniz and Paes for their letter 1 on our minicommentary 2 regarding the study by Lau et al 3 In that letter they talk about their recently published study highlighting the potential of ophthalmic artery (OA) Doppler as a complementary diagnostic tool of pre-eclampsia (PE). 4 The best diagnostic performance showed the 2nd systolic peak P2 and in particular the systolic peak ratio PR = P2/P1.
…”
mentioning
confidence: 99%
“…However, screening studies showed that assessment of these indices offers no significant benefit to routine screening which uses maternal characteristics to identify women at risk of HDP 7 . In contrast, impedance to peripheral blood flow assessed by ophthalmic artery Doppler can identify women at risk of HDP in all three trimesters of pregnancy 9–11 . Whether these findings suggest more established vascular disease in women at risk of HDP remains to be determined.…”
Section: Introductionmentioning
confidence: 99%